Communication needs regarding heart failure trajectory and palliative care between patients and healthcare providers: A cross-sectional study. - Jin-Sun Park; Kyoung-Woo Seo; Jung Eun Lee; Kyoung-Hwa Kim; Jeong-Ah Ahn (PLoS ONE)
Introduction Heart failure (HF) is a chronic condition with an unpredictable trajectory, making effective communication between patients and healthcare providers crucial for optimizing outcomes. This study aims to investigate and compare the communication needs regarding HF trajectory and palliative care between patients and healthcare providers and to identify factors associated with the communication needs of patients with HF. Methods A cross-sectional study design was employed, involving 100 patients with HF and 35 healthcare providers. Data were collected using structured questionnaires assessing communication needs, health literacy, self-care behavior, and social support. Statistical analyses were performed, including Spearman's rank correlation, Pearson's correlation, and multiple regression analyses. Results Patients prioritized communication related to device-related questions, whereas healthcare providers focused more on aspects of HF in daily life. Both groups ranked end-of-life communication as the lowest priority. The communication needs of patients were positively correlated with health literacy (r = 0.27, p = .007), self-care behavior (r = 0.32, p = .001), and social support (r = 0.24, p = .016). Multiple regression analyses indicated that self-care behavior was a significant factor influencing the communication needs of patients (β = 0.27, p = .011). Conclusions Enhanced patient-centered communication strategies are required to address the communication priority gaps between patients and healthcare providers. Improving health literacy, supporting self-care behaviors, and leveraging social support are critical in meeting patients' communication needs. Tailored communication training for healthcare providers can bridge this gap and improve overall HF management.